Multiple Coulomb scattering method to reconstruct low-energy gamma–ray direction in the GAMMA-400 space-based gamma–ray telescope. Issue 10 (15th May 2019) - Leonov, A.A.; Galper, A.M.; Topchiev, N.P.; Bakaldin, A.V.; Dalkarov, O.D.; Dzhivelikyan, E.A.; Egorov, A.E.; Kheymits, M.D.; Mikhailov, V.V.; Picozza, P.; Sparvoli, R.; Suchkov, S.I.; et al.
Abstract: The GAMMA-400 currently developing space-based gamma-ray telescope is designed to measure the gamma-ray fluxes in the energy range from ∼20 MeV to several TeV in the highly elliptic orbit (without shadowing the telescope by the Earth) continuously for a long time. The physical characteristics of the GAMMA-400 gamma-ray telescope, especially the angular and energy resolutions (at 100-GeV gamma rays they are ∼0.01° and ∼1%, respectively), allow us to consider this space-based experiment as the next step in the development of extraterrestrial high-energy gamma-ray astronomy. In this paper, a method to improve the reconstruction accuracy of incident angle for low-energy gamma rays in the GAMMA-400 space-based gamma-ray telescope is presented. The special analysis of topology of pair-conversion events in thin layers of converter was performed. Applying the energy dependence of multiple Coulomb scattering for pair components, it is possible to estimate the energies for each particle, and to use these energies as weight in the angle reconstruction procedure. To identify the unique track in each projection the imaginary curvature method is applied. It allows us to obtain significantly better angular resolution in comparison with other methods applied in current space-based experiments. When using this method for 50-MeV gamma rays the GAMMA-400 gamma-ray telescope angular resolution is about 4°.